ANALISIS STRUKTUR BOX GIRDER JEMBATAN FLY OVER RAWA BUAYA SISI BARAT TERHADAP GEMPA - Aditya Fajar Meidiansyah; M. Yanuar J. Purwanto; Muhammad Fauzan (Jurnal Teknik Sipil dan Lingkungan, 2016)
The Rawabuaya flyover bridge is an option to overcome the traffic jam that often happens in the Rawabuaya area. It has an extremely vital function to disentangle the traffic congestion; therefore, the structure must be strong in holding the on-going load, specifically the seismic load. The seismic load is dangerous to a structure because it has period that causes the structure to repeatedly shaken. If the movements happened continually, the structure will collapse ― depending on how much earthquake load that is being loaded on the structure. Therefore, it is essential to conduct a structural analysis on the earthquake resistance level of the Rawabuaya flyover bridge based on the "Standar Perencanaan Ketahanan Gempa Untuk Struktur Bangunan Gedung dan Non-Gedung" RSNI 03-1726-2010 and "Peta Zonasi Gempa Indonesia 2010" to know further about the on-going deformation. This research was done thoroughly by recognizing the maximum forces in the combination of ultimate loads based on the most recent rules of encumbering, including the rules regarding the seismic load. The maximum forces in the combination of ultimate loads were compared with the forces' nominal values, especially those related to the seismic load. From the research, it was concluded that the values of the maximum forces in the combination of ultimate loads had the combined seismic load worked on the upper structure of box girder as well as on the structure beneath the pier of Rawabuaya flyover bridge with a maximum moment values of 800300.80 KNm applied to Pier P6B with the combination of the singular ultimate load, additional dead load, pre-stressed load, and “T” truck load. Impairment to the structure was found to happen if the combination of the ultimate load was forced to work continuously on the Rawabuaya flyover bridge. Meanwhile, the result of the compared maximum forces in the combination of ultimate load with the values of nominal forces indicated that the Rawabuaya flyover bridge had a large amount of seismic load with 10% difference. It meant that this structure was able to resist 90% of ultimate seismic load, which required the usage of reinforcements on the upper structure of box girder as well as on the structure beneath the pier to increase the concrete stress power and the tendon on the upper structure of box girder to increase the tensile of the concrete. Keywords: prestressed box girder, structural analysis, seismic load, force